2016
DOI: 10.1186/s12884-016-0841-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of some birth defects in Korea, 2009–2010

Abstract: BackgroundBirth defects are a leading cause of neonatal and infant mortality, and several studies have indicated an increase in the prevalence of birth defects; more recent investigations have suggested that the trends of some defects are increasing in rapidly industrialized areas. This study estimates the prevalence rate and types of birth defects in Korea.MethodsThis study used medical insurance benefit data of 403,250 infants aged less than one year from the National Health Insurance Corporation from seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 39 publications
3
19
2
Order By: Relevance
“…We identified apparent upward trends in the prevalences of urogenital anomalies, particularly, renal dysplasia, renal agenesis, undescended testis, and hypospadias. In Korea, previous studies have reported increases in the prevalence of some urogenital anomalies [ 13 , 14 ]. Kim et al indicated that the incidence of cryptorchidism and hypospadias increased in Korea from 2000 to 2005 (5.01 to 17.43 per 10,000 and 1.40 to 3.28 per 10,000 births, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified apparent upward trends in the prevalences of urogenital anomalies, particularly, renal dysplasia, renal agenesis, undescended testis, and hypospadias. In Korea, previous studies have reported increases in the prevalence of some urogenital anomalies [ 13 , 14 ]. Kim et al indicated that the incidence of cryptorchidism and hypospadias increased in Korea from 2000 to 2005 (5.01 to 17.43 per 10,000 and 1.40 to 3.28 per 10,000 births, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, cryptorchidism increased from 5.01 to 17.43 per 10,000 births and hypospadia also increased from 1.40 to 3.28 per 10,000 births between 2000 and 2005 [ 13 ]. In addition, a Korean study based on medical insurance claims data for 2009–2010 showed a 14-fold increase in hypospadias and epispadias, a 12-fold increase in atrial septal defects, a 11-fold increase in undescended testis as compared with 1993–1994 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1–3 However, another study reported the prevalence of birth defects in Korea in 2009 and 2010 as 5.8%. 13 Although there might be methodological limitations and variations, the prenatal and postnatal detection rates of birth defects in live births seems to be increasing. In this study, 22.8% of infant deaths in Korea were related to birth defects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mandatory folic acid supplementation in Korea might help reduce nervous system anomalies because the youngest age group is less likely to take periconceptional folic acid supplementation and the overall prevalence of spina bifida in Korea is showing a tendency to increase. 13 …”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CHD among Asians has been reported to be 50% higher compared to the Caucasians and Blacks, especially for severe and complex CHD that have a high infant mortality [9]. In Asian countries, the incidence of ASD is high in Malaysia (9.6%) [10], Korea (44.2%) [11] and Thailand (43%) [12]. Studies have described that approximately 5% of children with serious CHD dies without undergoing any procedures [13].…”
Section: Introductionmentioning
confidence: 99%